(untitled) - Finkelstein, Leo (Boston, 2006)
Pocket Book of English Grammar for Engineers and Scientists is geared specifically to the needs of engineering and science practitioners and students, although it is also appropriate for anyone doing technical or business writing. The book is unique among grammar manuals not only because of its straightforward, simplified organizational structure, but also because of its use of innovative tools and examples.
Keywords: English language,Technical writing,Anh ngữ thực hành,Kỹ thuật viết; Grammar,Ngữ pháp